2023
DOI: 10.1021/acsmacrolett.3c00072
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transformation of Polyacrylonitrile Accelerated by the Formation of Ultrathin Nanosheets in a Metal–Organic Framework

Abstract: In this study, polyacrylonitrile (PAN) nanosheets with unimolecular thickness were successfully synthesized by cross-linking polymerization in the 2D nanospaces of a metal–organic framework. In contrast to 1D and 3D analogues, crystallization could be inhibited by the topological constraint of the ultrathin 2D network structure, allowing for an efficient thermal transformation reaction of PAN. The amorphous nature of the PAN nanosheets led to an increase in the access of oxygen molecules to the polymer chains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…As shown in Figure d, differential scanning calorimetry heating traces of 1D, 2D, and 3D PAN showed that the 1D and 3D PAN have clear melting peaks; in contrast, the 2D PAN showed a broad peak diagnostic of its amorphous nature. 2D PAN remains amorphous in the bulk state, facilitating thermal dehydroaromatization reactions to form a conjugated ladder structure …”
Section: Monomer Nanoconfinement In 2d Hostsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure d, differential scanning calorimetry heating traces of 1D, 2D, and 3D PAN showed that the 1D and 3D PAN have clear melting peaks; in contrast, the 2D PAN showed a broad peak diagnostic of its amorphous nature. 2D PAN remains amorphous in the bulk state, facilitating thermal dehydroaromatization reactions to form a conjugated ladder structure …”
Section: Monomer Nanoconfinement In 2d Hostsmentioning
confidence: 99%
“…The dimensionality of the MOF nanopores is transcribed to the polymer structure. When monomers are polymerized in the 2D nanospace of a pillared-layer MOF are separated by coordination layers with the distance of the “pillar” molecules, 2DPMs were prepared on a gram-scale. ,, A similar synthetic trial of a 2DPM was performed in an earlier study using sodium montmorillonite clay; however, the obtained polymer was neither cross-linked nor isolated by removing the host . When we performed the cross-linking polymerization of styrene and ethylene glycol dimethacrylate (cross-linker) in a pillared-layer MOF, [Ni­(Hbtc)­(bpy)] n (btc = 1,3,5-benzenetricarboxylate, bpy = 4,4′-bipyridyl), we obtained 2D polystyrene (2D PS) after MOF removal (Figure a) .…”
Section: Monomer Nanoconfinement In 2d Hostsmentioning
confidence: 99%
See 3 more Smart Citations